Similarity and Finite Difference Solution on Biomagnetic Flow and Heat Transfer of Blood-Fe3O4 through a Thin Needle. (22nd December 2022) - Alsenafi, Abdulaziz; Ferdows, M.
Abstract : A magnetic fluid is composed of a base fluid and magnetic particles, where magnetic particles are carefully distraught in the base fluid. Here, we will assume that blood is the base fluid that exhibits electrical conductivity and polarization properties and Fe3 O4 as magnetic particles. The addition of Fe3 O4 into the blood can remarkably ameliorate the properties of the blood's thermal conductivity. Such physical aspects can play a vital role in biomedical and bioengineering. The presented model studies the biomagnetic fluid flow, such as blood that contains magnetic particles through a thin needle in the appearance of a strong magnetic dipole. First, the governing equations are transformed using similarity transformation into a system of dimensional differential equations, which are then nondimensionalized. The system of nondimensional equations is then solved numerically using a finite difference method. By analyzing the results, we find that the axial flow decreases for the ferromagnetic number, magnetic field number, and Eckert number, while the temperature increases with volume fraction, where the size of the needle plays a significant role. Finally, the results also indicate that the presence of ferromagnetism significantly influences the skin friction coefficient. Our presented results will also be compared with existing literature that is similar to our work.